A Comparative Evaluation of Public Road Transportation Systems in India Using Multicriteria Decision-Making Techniques. (24th October 2020) - Kumar, Anand; Singh, Gurmeet; Vaidya, Omkarprasad S.
Abstract : In this paper, we evaluate the performance of major public road transport organizations in India. The contribution of the paper lies in integrating four multicriteria decision-making (MCDM) techniques to assess the relative performance of public road transportation systems on twenty-three criteria across two consecutive years. The paper classifies the criteria into functional heads and establishes the relative importance of heads using the analytical hierarchical process (AHP). The efficiency scores of each organization referred to as a decision-making unit (DMU) were computed for the classified heads using the Data Envelopment Analysis (DEA) approach. The multicriteria optimization and compromise solution technique "VlseKriterijumska Optimizacija I Kompromisno Resenje" (VIKOR) was used to assign a final rank to each of the DMUs using computed efficiency scores and established weights. Finally, we analyzed the performance of the DMUs across the two consecutive years using the Malmquist Productivity Index (MPI). Our key findings are as follows: First, the performance of all DMUs has improved in the second year with respect to the first year; second, significant improvement is observed in the "expenses" functional head which carries a substantial weight among the functional heads; third, barring few DMUs, the performance of the majority of DMUs has worsened in the "accident" functional head; fourth, while few DMUs have been consistently very good performers in both the years, there are also few DMUs which have consistently performed poorly in both the years. The inferences drawn from the study can be leveraged for future policy formulations by the state government and local municipal corporations and for sharing best practices among the DMUs.